2019
DOI: 10.21608/ejmm.2019.282670
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae in Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease in Menoufia University Hospitals

Abstract: Background: Klebsiella pneumoniae is an important etiological agent of Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD) which is a progressive, debiliting lung disease with multiple co-morbidities. Infections with multidrug resistant (MDR) K. pneumoniae strains are usually associated with high morbidity and mortality, long hospital stay and high healthcare costs. Objectives: to determine the incidence of aerobic bacteria isolated from patients with COPD, to detect plasmidmediated quinolones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…In accordance with these findings, a Korean study analyzed patients with severe ECOPD and found a direct correlation between severity of airway obstruction and bacterial identification rate, with P.aeruginosa and strept.pneumoniae showing strongest association [20]. Also, it was reported that a highly significant relationship was detected between severity of ECOPD and K.pneumoniae isolation [21]. Other investigations of the relationship between bacteriologic etiology and lung function in patients with ECOPD demonstrated that P.aeruginosa and enterobacteriaceae were predominant in patients with severely impaired lung function [22].…”
Section: Discussionmentioning
confidence: 59%
“…In accordance with these findings, a Korean study analyzed patients with severe ECOPD and found a direct correlation between severity of airway obstruction and bacterial identification rate, with P.aeruginosa and strept.pneumoniae showing strongest association [20]. Also, it was reported that a highly significant relationship was detected between severity of ECOPD and K.pneumoniae isolation [21]. Other investigations of the relationship between bacteriologic etiology and lung function in patients with ECOPD demonstrated that P.aeruginosa and enterobacteriaceae were predominant in patients with severely impaired lung function [22].…”
Section: Discussionmentioning
confidence: 59%